Global reemergence of enterovirus D68 as an important pathogen for acute respiratory infections. (3rd December 2014) - Imamura, Tadatsugu; Oshitani, Hitoshi
Summary We previously detected enterovirus D68 (EV‐D68) in children with severe acute respiratory infections in the Philippines in 2008–2009. Since then, the detection frequency of EV‐D68 has increased in different parts of the world, and EV‐D68 is now recognized as a reemerging pathogen. However, the epidemiological profile and clinical significance of EV‐D68 is yet to be defined, and the virological characteristics of EV‐D68 are not fully understood. Recent studies have revealed that EV‐D68 is detected among patients with acute respiratory infections of differing severities ranging from mild upper respiratory tract infections to severe pneumonia including fatal cases in pediatric and adult patients. In some study sites, the EV‐D68 detection rate was higher among patients with lower respiratory tract infections than among those with upper respiratory tract infections, suggesting that EV‐D68 infections are more likely to be associated with severe respiratory illnesses. EV‐D68 strains circulating in recent years have been divided into three distinct genetic lineages with different antigenicity. However, the association between genetic differences and disease severity, as well as the occurrence of large‐scale outbreaks, remains elusive. Previous studies have revealed that EV‐D68 is acid sensitive and has an optimal growth temperature of 33 °C. EV‐D68 binds to α2, 6‐linked sialic acids; hence, it is assumed that it has an affinity for the upper respiratory track where these glycans are present. However, the lack of suitable animal model constrains comprehensive understanding of the pathogenesis of EV‐D68. © 2014 The Authors. Reviews in Medical Virology published by John Wiley & Sons Ltd.